2008
DOI: 10.1007/s12221-008-0100-7
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of sounds generated from vapor permeable water repellent fabrics by low-speed frictions

Abstract: To investigate the sound properties by low-speed frictions (0.2 m/s and 0.5 m/s) which occur when two fabrics are rubbed by wearer's slow movement, six specimens are selected by cluster analysis among seventy-one vapor permeable water repellent fabrics for outdoor sportswear. Their sound spectra are obtained from the FFT analysis. Physical sound properties (LPT, ΔL, Δf) and Zwicker's psychoacoustic parameters -loudness(Z), sharpness(Z), roughness(Z), and fluctuation strength(Z) -are calculated from the sound s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 12 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…Cho et al [11] have investigated the changes in acoustic properties of the military uniform by wearer's movement speeds. Chunjeong Kim et al [12] more in-depth analyzed the acoustic properties of vapor permeable water repellent fabric sounds generated by low-speed frictions (0.2 m/s and 0.5m/s) and investigated the relationships between the sound properties and the mechanical properties of the fabrics. Recently, Cho et al [13] [14] proposed a new model capable of predicting frictional sounds of woven fabrics, knitted fabrics and vapor permeable water repellent fabrics by measuring the relationships between their sound parameters and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Cho et al [11] have investigated the changes in acoustic properties of the military uniform by wearer's movement speeds. Chunjeong Kim et al [12] more in-depth analyzed the acoustic properties of vapor permeable water repellent fabric sounds generated by low-speed frictions (0.2 m/s and 0.5m/s) and investigated the relationships between the sound properties and the mechanical properties of the fabrics. Recently, Cho et al [13] [14] proposed a new model capable of predicting frictional sounds of woven fabrics, knitted fabrics and vapor permeable water repellent fabrics by measuring the relationships between their sound parameters and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…The fabric frictional sound was generated when the fabric is rubbed against another fabric because of wearer's movement. 5 According to US Army's Field Manual, noise is one of the essential factors avoided for camouflage and survival. It warns that the noise generated from the movement can attract the enemy's attention, so suggests slowing the pace as much as possible to minimize the sound and that using background noise to cover the noise from the movement.…”
mentioning
confidence: 99%
“…Previous studies 5,7 have been carried out to reduce the frictional noise of coated fabrics, but none of them have considered the effects of coating conditions such as resin concentrations and curing temperatures on noise reduction. The previous studies only showed that frictional sounds of various combat uniform fabrics had significant correlation with some mechanical properties measured by the Kawabata Evaluation System.…”
mentioning
confidence: 99%